Sosialisasi dan Edukasi Keselamatan Berlalu-Lintas Serta Bahaya Konsumsi Narkoba - Pramudita, Dismas Persada Dewangga (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aims to enhance adolescents’ understanding of the dangers of drug abuse and the importance of ethical driving as part of efforts to prevent traffic accidents. The activities were carried out through counseling sessions, interactive discussions, and case studies on proper driving safety procedures. A community education approach was used to deliver factual information regarding the medical, psychological, and social impacts of drug use, as well as the legal risks associated with traffic violations. A communicative approach was applied through QA sessions that encouraged participants to share their insights and experiences related to drugs and driving behavior. The results show a significant increase in participants’ understanding of the dangers of drugs, addiction consequences, and key driving safety principles, including greater awareness of risky behaviors. This program highlights the importance of continuous preventive education and collaboration with schools and local communities as strategies to foster healthy, disciplined, and responsible youth.